Detection of methicillin and mupirocin resistance in staphylococcal hospital isolates with a touchdown multiplex polymerase chain reaction - Sareyyüpoğlu, B; Ozyurt, M; Haznedaroğlu, T; Ardiç, N (Folia microbiologica, 2008)
Staphylococcal hospital isolates (n = 166) were tested in a touchdown multiplex-polymerase chain reaction assay for the identification of methicillin and mupirocin resistance and discrimination of S. aureus (femA gene) from coagulase negative staphylococci and other bacteria. All isolates harbored the 16SrDNA (Staphylococcus genus specific internal control) gene, and 130 (78 %) the mecA (methicillin resistance) gene. Fifty-seven (44 %) of these were determined as methicillin-resistant S. aureus, while the remaining 73 (56 %) were methicillin-resistant coagulase-negative staphylococci. Seventy-five (45 %) isolates harbored the ileS-2 (high-level mupirocin resistance) gene and were determined as mupirocin-resistant. This assay represents a simple, rapid, reliable approach for the detection and discrimination of methicillin-and mupirocin-resistant staphylococci.
Keywords: Staphylococcus; RNA ribozomální 16S; senzitivita a specificita; Bacterial Proteins; Staphylococcal Infections; rezistence na methicilin; lidé; mupirocin; Anti-Bacterial Agents; nemocnice; polymerázová řetězová reakce; methicilin; Polymerase Chain Reaction; DNA, Bacterial; Methicillin; DNA bakterií; bakteriální proteiny; mnohočetná bakteriální léková rezistence; Drug Resistance, Multiple, Bacterial; Sensitivity and Specificity; antibakteriální látky; Methicillin Resistance; Humans; RNA, Ribosomal, 16S; stafylokokové infekce; Mupirocin; Hospitals